An analysis of derived benefit from saving account: An Islamic perspective - Ahmad, Shofian; Laluddin, Hayatullah; Ahmad, Md. Yazid (Medwell Publishing, 2012)
Banking industry in its attempt to attract more customers, hence capital offer various forms of benefits. These benefits basically take two form; direct and indirect. The first type of benefits are represented by provision of dividend to depositors whereas, the second type of benefits are represented by offering of insurance, sale on discount rate when using the debit card, annual gift and lucky draw. such entitlement is dependent on having saving account in the bank. Without having saving account one would not have access to such facilities and offer. This research focuses mainly on the issue of indirect benefits and their status from Shari'ah perspective. Library research research method is used in this research due to the nature of its subject. The hypothesis of the research revolves around the status of indirect benefits offered by banks from Shari'ah perspective and the distinctive of such benefits offered by Islamic banking. The finding of the research shows that the benefit direct or indirect received by customer in Islamic banking have various features. All theses benefits are received through depositing in the bank.